Optimalisasi Komitmen Organisasi Karyawan Bagian Produksi PT. Hino Motors Manufacturing Indonesia Kabupaten Purwakarta Melalui Pengembangan Karier dan Kepuasan Kerja - Habibah, Siti; Abdurahman, Khaerul Rizal; Pratama, Wisnu Bayu (J-MAS (Jurnal Manajemen dan Sains), 2024)
The success of such a company lies in the role of every employee who has a strong commitment to its organization, because each employee whose strong commitments mean that they are willing to engage themselves with the company is characterized by a strong level of loyalty and dedication to the company. Then, from there, the commitment should be observed by every company. Some of the factors that can make the organization's commitment strong are how the company looks at the career development and job satisfaction of each of its employees. This research aims to find out the relationship between career development and job satisfaction and the organizational commitment of employees of the Production Division at PT. Hino Motors Manufacturing Indonesia in the district of Purwakarta. The research uses quantitative approaches and nonprobability sampling. Data analysis techniques using validity tests, reliability tests, classical assumption tests, double linear regression tests, and hypothesis tests are interpreted by interpreting the output tables of the Statistical Package for Social Science (SPSS) software program version 26. The results of this research show that career development has a partial influence on employee organization commitment, and job satisfaction has a partial impact on employee organization commitment. Furthermore, career development and employment satisfaction have a simultaneous effect on the commitment of employees in the production division of PT. Hino Motors Manufacturing Indonesia, Purwakarta district. This means that the more companies pay attention to employee career development, the higher levels of employee satisfaction can further strengthen the organization's commitment.